PENGENALAN INTERNAL RATE OF RETURN DALAM INVESTASI PADA SISWA SMA NEGERI BALUNG - Sari Dewi Oktavianti, Wulandari; Rosana, Manna; Andariana, Yulia; Isabella, Nurullah; Bachtiar, Fatim Rosa; Wahyudi, Muhammad Nur; Fajri, Gilang; Raharjo, Marcerio Tri Putra; Faisandra, Mariska Amalia; Saputra, Aditya Fernanda Raihan; Gunasti, Amri (Jurnal Abdi Insani, 2024)
Education is a crucial aspect in the development process that aims to improve the quality of human and economic resources. SMA Negeri Balung, as one of the leading schools in Balung Sub-district, implements a Full Day School program. Unfortunately, there is no specific subject on investment. In this service activity, students are introduced to the concept of Internal Rate of Return (IRR) in investment. The purpose of this activity is to increase students' understanding of investment and its application in everyday life. Students are able to simulate investment analysis on construction project case studies. The activity method includes the delivery of coordination meetings, making materials, making assignment letters and proposals, surveying the location of the service, submitting assignment letters and proposals, implementing the service and evaluating the success of the service. This activity was carried out at the Balung Jember State Senior High School (SMA) on April 24, 2024. Before the implementation of the activity, the average level of student understanding of the Internal Rate of Return (IRR) was 48. The results of the activity showed a significant increase in student understanding, where the average post-test score was 79. This activity has increased students' ability by 31 points. The conclusion of this activity is that the introduction of IRR successfully improved students' knowledge of investment and its future applications. Students showed active participation during the material delivery session.